The construction of the other in a Brazilian weekly magazine - Prado, José Luiz Aidar (Brazilian journalism research, 2005)
Postmodern thought considers, in general, otherness as absolute. Bernstein (1991) denies such absoluteness, as there is always a possibility of failure in doing justice to the otherness; we should assume the responsibility of acknowledging the otherness of the Other. In this article I propose to examine the possibility of regarding the relationship between the reader and the media as ethical, that is, respecting otherness. To do so, we counterbalance the bernsteinian view with other stances, confronting communitarian authors and non-communitarian ones. What would be the meaning of the Reader’s unfaithfulness in terms of a reading and communication contract? We intend to answer such questions on the basis of a thematic and discursive examination of the Brazilian weekly magazine Veja (approximately one million issues weekly), particularly analyzing how otherness is constructed in the cover stories dealing with topics such as violence and punishment, wealth and poverty.